High accuracy of an ELISA test based in a flagella antigen of Leishmania in serodiagnosis of canine visceral leishmaniasis with potential to improve the control measures in Brazil - A Phase II study. - Lairton Souza Borja; Lívia Brito Coelho; Matheus Silva de Jesus; Artur Trancoso Lopo de Queiroz; Paola Alejandra Fiorani Celedon; Nilson Ivo Tonin Zachin; Edimilson Domingos Silva; Antônio Gomes Pinto Ferreira; Marco Aurélio Krieger; Patrícia Sampaio Tavares Veras; Deborah Bittencourt Mothé Fraga (Public Library of Science (PLoS), 2018)
BACKGROUND:Canine Visceral leishmaniasis (CVL) is a serious public health problem, thus for its control, the Ministry of Health in Brazil recommends the rapid diagnosis and euthanasia of seropositive dogs in endemic areas. Therefore, our group had previously selected six recombinant proteins (rLci1, rLci2, rLci4, rLci5, rLci8, and rLci12) due to their high potential for CVL diagnostic testing. The present study aims to produce an immunodiagnostic test using the aforementioned antigens, to improve the performance of the diagnosis of CVL recommended by Brazilian Ministry of Health. METHODOLOGY/PRINCIPAL FINDINGS:To evaluate the recombinant proteins in the serological assays, positive and negative samples were selected based on parasitological test (culture) and molecular test (qPCR) of splenic aspirate. Initially, we selected 135 dog serum samples, 73 positives (symptomatic and asymptomatic) and 62 negatives to screen recombinant proteins on ELISA platform. Then, for rLci5 ELISA validation, 361 serum samples collected in a cross-sectional study were selected, being 183 positives (symptomatic and asymptomatic) and 178 negatives. In the screening of the recombinant proteins, rLci5 was the only protein to present a performance statistically higher than the performance presented by EIE-LVC test, presenting 96% (IC 95%; 85-99%) vs. 83% (IC 95%; 69-92%) of sensitivity for symptomatic dogs, 71% (IC 95%; 49-97%) vs. 54% (IC 95%; 33-74%) for asymptomatic dogs and 94% (IC 95%; 83-99%) vs, 88% (IC 95%; 76-95% of specificity. Thus, the rLci5 protein was selected to compose a final ELISA test. Validation of rLci5 ELISA showed 87% (IC 81-91%) of sensitivity, 94% (IC 95%; 90-97%) of specificity and 90% accuracy. Testing the EIE-LVC with the same validation panel, we observed a lower performance when compared to ELISA rLci5 (sensitivity of 67% (IC 95%; 59-74%), specificity of 87% (IC 95%; 81-92%), and accuracy of 77%). Finally, the performance of current CVL diagnostic protocol recommended by Brazilian Ministry of Health, using DPP-LVC as screening test and EIE-LVC as confirmatory test, was compared with a modified protocol, replacing EIE-LVC by rLci5 ELISA. The current protocol presented a sensitivity of 59% (IC 95%; 52-66%), specificity of 98% (IC 95%; 95-99%) and accuracy of 80% (IC 95%; 76-84%), while the modified protocol presented a sensitivity of 71% (IC 95%; 63-77%), specificity of 99% (IC 95%; 97-100%) and accuracy of 86% (IC 95%; 83-89%). CONCLUSION:Thus, we concluded that rLci5 ELISA is a promising test to replace EIE-LVC test and increase the diagnostic performance of CVL in Brazil.